Model Pembimbingan Konferensi 3-2-1 Berbantuan Video-Stimulated Recall untuk Meningkatkan Kompetensi Pedagogik dan Profesional Calon Guru Fisika - Fitria, Elfiana; Rusilowati, Ani; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2020)
The implement of Conference 3-2-1 (K 3-2-1) guidance model with Video-stimulated recall (VSR) is being done as a way to increase educator quality, which is the candidate of physics teachers when doing teaching practice. Teaching education through pre-service training in LPTK gives provisions to get mastering and delivering learning materials well to students. This research has a purpose to get information about the implementation of K 3-2-1 guidance model with VSR in increasing physics teachers’ pedagogical and professional competence. This research is single subject research patterned action research. The approach in this research is qualitative research. The implementation of K 3-2-1 guidance model includes of explanation of three aspects of excesses, two aspects of weaknesses, and one constructive advice about teacher candidates’ teaching practice. Result of this research shows that there is increased pedagogic and profesional competences after being given K 3-2-1 guidance with VSR. The practitioner shows very positive respond towards the implementation of K 3-2-1 guidance model with VSR, by score percentage 91,18%. The researcher concluded that K 3-2-1 guidance model with VSR is able to increase physics teacher candidates pedagogical and professional competence as well as teacher candidates feel very helped after K 3-2-1 guidance with VSR was applied.